Percutaneous Placement of Iliosacral Screws Under the Guidance of Axial View Projection of the S1 Pedicle: a Case Series - Yingchao Yin (Nature Portfolio, 2017)
Abstract The aim of this study was to evaluate the safety and efficacy of percutaneous placement of iliosacral screws under the guidance of axial view projection of the S1 pedicle clinically. This case series includes 58 consecutive unstable pelvic injury patients, which were treated with iliosacral screws between July 2011 and July 2016. Patients were divided into two groups: normal sacrum (n = 31) and dysmorphic sacrum (n = 27). A single orthopedic surgeon operated on all patients, with percutaneous placement of iliosacral screws under the guidance of axial view projection of the S1 pedicle. The time needed for screw insertion and the radiation exposure time were recorded. Chi-squared test and Student t-test were used to analyze the differences between the two groups. Sacral dysmorphism was present in 47% of patients. The median time for screw insertion and radiation exposure time in these two groups showed no statistical difference (P > 0.05). No clinical complications or malpositioned screws occurred in any case. Preoperative pelvic CT is necessary to determine the sacral osseous anatomy. In patients with either a normal or dysmorphic sacrum, iliosacral screws can be placed by this method with less radiation exposure and complications than in the conventional method.